Analysis of the effect of electro-discharge water treatment on its purification degree - Shaimerdenova, K.M.; Stoev, M.; Tusypbaeva, A.S.; Rakhmankyzy, A.; Sekerbaeva, G. (Publishing House of the KarSU named after E.A. Buketov, 2018)
This article discusses the study of the analysis of the effect of electric discharges on the degree of water purification. A description of the technique for measuring specific electrical conductivity using a conductivity meter is presented. The technical process operation procedure for obtaining purified and decontaminated water during the electro-discharge treatment is given. In the course of the research, the change in the salinity and the specific electrical conductivity of the tap water and natural water samples after the treatment with the electric pulse method was studied. The experiments took into account the processing time and the number of electric pulse discharges.
Keywords: water purification; water quality; electrical conductivity; electric pulse method; pulse discharge